1994
DOI: 10.1159/000292441
|View full text |Cite
|
Sign up to set email alerts
|

Value of Symphysiotomy in Obstructed Labour Management and Follow-Up of 31 Cases

Abstract: Experience of 32 cases of symphysiotomy carried out in Mozambique and in Botswana is reviewed. Of all cases only 1 was lost to follow-up. The observation period varied from 7 days to 6 months. Among 31 cases examined at discharge or on return for check-up few complications occurred. Vaginal laceration occurred in 3 cases, haematuria in 1 case and wound infection in 1 case. In 2 cases there was significant postoperative pain causing gait problems, but in no case were there significant problems with pain at disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
6
1
5
Order By: Relevance
“…The results from the present study and previous follow-up studies indicate that symphysiotomy confers an acceptable level of complaints in the long run [10], [16], [32], [36], [38]. Lasbrey assessed pain in the symphysis pubis, groin, hip, thigh, sacro-iliac joint and stress incontinence, mostly associated with physical activity, and found that these problems were small and did not interfere with day-to-day activities [36].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The results from the present study and previous follow-up studies indicate that symphysiotomy confers an acceptable level of complaints in the long run [10], [16], [32], [36], [38]. Lasbrey assessed pain in the symphysis pubis, groin, hip, thigh, sacro-iliac joint and stress incontinence, mostly associated with physical activity, and found that these problems were small and did not interfere with day-to-day activities [36].…”
Section: Discussionsupporting
confidence: 59%
“…Infertility after symphysiotomy was not addressed in the present study, and the woman who reported incontinence was apparently subject to an incorrect judgement of the degree of cephalopelvic disproportion. Pain or tenderness over the symphysis pubis when walking long distances was observed in this study, but not reported nor mentioned as a parameter in previous follow-up studies [4], [10], [13], [32]–[38]. Dyspareunia was registered in 17,2% (CS group) and 29,4% (S group) of the women in this study, unfortunately women with normal vaginal deliveries were not asked about this.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Not stated Sabriá Ayiné (1949) 55 Spain 68 Botswana Not stated 25 0 0 Mola (1995) 69 Papua palpable per abdomen, a trial of vacuum extraction was done before proceeding to symphysiotomy. However, the trial of vacuum extraction was omitted in cases with fetal distress 39 .…”
Section: Management Of Labour and Mode Of Deliverymentioning
confidence: 99%
“…Time interval Women Symphyseal width (cm) n Mean Corrected Mean (Range) Kehrer (1913) 31 33 days 9 68 25 0 0 0 --Mola (1995) 69 62 -0 ---Pape (1999) 7 27 the symphyseal joint in a woman who had undergone symphysiotomy showed ''collagenous connective tissue containing a few vascular channels'' 76 .…”
Section: Referencesmentioning
confidence: 99%